Mathematical Modelling in Epidemiology: A Numerical study - Kaur, Mitveen (My University, 2019)
In order to understand the complexity of real world processes, one need to model these processes mathematically. In this thesis, we review a epidemic compartmental models and their classi fications. The aim of our approach is to develop an intuitive understanding of epidemic models and adapt a new technique Monte Carlo simulations for the validation of various epidemic model. A new model SEIQR has been introduced and results are validated using Runge Kutta method and Monte Carlo simulations
Keywords: Mathematical modelling; SEIQ model; SEIQR model; Epidemic models; Compartmental models; Monte Carlo simulations; Quarantine